1979
DOI: 10.1099/00221287-112-1-77
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Metabolism in Rhizobium trifolii: Identification and Symbiotic Properties of Mutants

Abstract: ~Crude extracts of Rhizobium trifolii strain 7000 contained enzymes of the Entner-Doudoroff and pentose phosphate pathways. No phosphofructokinase (EC 2.7.1 . 1 1) activity and only a low activity of fructose-1,6-bisphosphate aldolase (EC 4.1.2.13) were found, suggesting that the Embden-Meyerhof-Parnas pathway was not physiologically important in this strain.Independent carbohydrate-negative mutants of R. trifolii were isolated and characterized as deficient in glucokinase (glk; EC 2.7.1 .2), fructose uptake (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 29 publications
9
96
0
Order By: Relevance
“…The latter study of R. leguminosarum mutants which were defective in sugar utilization suggested that the capacity to utilize C6 or C1 sugars, which are the major components of the plant photosynthate, was not essential for the establishment of an effective symbiosis. This finding was in accord with the data of Ronson & Primrose (1979); however, Duncan (1981) reported that a fructokinase mutant of R. meliloti was ineffective in symbiotic N2 fixation.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…The latter study of R. leguminosarum mutants which were defective in sugar utilization suggested that the capacity to utilize C6 or C1 sugars, which are the major components of the plant photosynthate, was not essential for the establishment of an effective symbiosis. This finding was in accord with the data of Ronson & Primrose (1979); however, Duncan (1981) reported that a fructokinase mutant of R. meliloti was ineffective in symbiotic N2 fixation.…”
Section: Introductionsupporting
confidence: 72%
“…The nutritional and symbiotic properties of bacterial mutants with specific defects in their capacities to utilize carbon compounds have been examined in Rhizobium trifolii (Ronson & Primrose, 1979;Ronson et al, 1981), R . meliloti (Duncan, 1981) and R .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other Rhixobitlm exoB mutants, CallO is able to grow on galactose as sole carbon source, in contrast to E. coli galE mutants, where galactose as the unique carbon source is lethal (Adhya, 1987 (Ronson & Primrose, 1979) and R . meliloti (Arias & Cervenans ky, 1986).…”
Section: Symbiotic Properties Of the Exob Mutantmentioning
confidence: 99%
“…Regulation of N2 fixation in legumes by fixed N does not seem to be at the level of nitrogenase synthesis (23; D. Noel and W. J. Brill, manuscript in preparation), but rather is at the level of nodulation. In the case of R. trifolii and clover, fixed N seems to prevent the lectin from being available to the bacteria (54 (186). A mutant of R. meliloti with a defective a-ketoglutarate dehydrogenase forms ineffective nodules (69).…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%